(untitled) (International Journal of Physiotherapy, 2019)
Background: Diabetes mellitus is one of the common public problems that its prevalence increase incredibly in the last three decades in KSA. The purpose of this work is to investigate the physical fitness of young male subjects with type 2 diabetes mellitus in KSA. Also, study the reliability of ALPHA-FIT test battery as easy, quick physical tools to test the physical fitness among Saudi society patients. Methods: Thirty males with type 2 diabetic were participated in the study and compared with thirty healthy volunteers represent the control group. The participants were investigated for their physical fitness by the ALPHA-FIT test battery. The seven categories of the test battery that forming the essential physical fitness for adults health and function. Results: The results of the study showed that there was a significant reduction in the physical fitness of the diabetic group compared with the control group. The cardiorespiratory fitness, the hand-grip is showing muscular strength, jump-to-reach indicating lower limbs power and strength, modified push-up owing to the trunk and upper limbs muscular endurance, standing on one-leg referring to balance state all results showing p-value < 0.05. In comparing both groups, there were no significant differences between diabetic and control groups regarding body mass index and waist circumference measures p-value > 0.05. Conclusion: Musculoskeletal and cardiorespiratory fitness were significantly lowered in patients with diabetes compared to age matching people. Health awareness and early physical intervention are recommended to prevent this reduction of fitness.